Pendampingan Orang Tua Membimbing Anak Belajar dari Rumah di Era Wabah Covid-19 - Jeaprileni A. Eli Manafe; Ezra Tari (UKI Press, 2021)
The online learning system requires parents to accompany their children more in learning. However, many parents still feel overwhelmed to explain the tasks given by the teacher online. Parents feel overwhelmed because they have to accompany their children and explain the tasks given by the teacher. Because not all parents are able to explain the task well so they are angry with their children. The goal of this study is to describe parental help during the COVID-19 epidemic. The author uses the Oebobo II Elementary School as an example. This research employs a qualitative descriptive-analytic technique. Decomposition of data obtained from informants in accordance with research questions. The study results found that learning facilities and infrastructure became primary sources in the learning process. The form of parental assistance provides learning facilities in laptops, internet quotas, and comfortable study rooms. So there is monitoring and control to help children who have learning difficulties. Smooth communication between teachers and parents is the leading way in a good learning process.